2016
DOI: 10.1002/mnfr.201600019
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone supplementation in postmenopausal women does not affect leukocyte LDL receptor and scavenger receptor CD36 expression: A double‐blind, randomized, placebo‐controlled trial

Abstract: Isoflavone supplementation for 12 weeks did not change LDLR and CD36 expression on leukocytes of PMW and did not affect body fat content and visceral adipose tissue (VAT), but slightly increased serum LDL-chol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…As such, there is a mechanism by which soy isoflavones could theoretically modulate circulating cholesterol levels. However, isoflavone supplements taken by postmenopausal women for 12 weeks did not alter the expression of genes associated with the LDLR and scavenger receptor CD36, both of which are important in regulating plasma LDL-C concentrations [105]. Further, no significant changes in body fat and visceral adipose tissue were detected; in fact, a potentially deleterious significant increase in LDL-C was observed [105].…”
Section: Interventional Studies Involving Soymentioning
confidence: 99%
See 1 more Smart Citation
“…As such, there is a mechanism by which soy isoflavones could theoretically modulate circulating cholesterol levels. However, isoflavone supplements taken by postmenopausal women for 12 weeks did not alter the expression of genes associated with the LDLR and scavenger receptor CD36, both of which are important in regulating plasma LDL-C concentrations [105]. Further, no significant changes in body fat and visceral adipose tissue were detected; in fact, a potentially deleterious significant increase in LDL-C was observed [105].…”
Section: Interventional Studies Involving Soymentioning
confidence: 99%
“…However, isoflavone supplements taken by postmenopausal women for 12 weeks did not alter the expression of genes associated with the LDLR and scavenger receptor CD36, both of which are important in regulating plasma LDL-C concentrations [105]. Further, no significant changes in body fat and visceral adipose tissue were detected; in fact, a potentially deleterious significant increase in LDL-C was observed [105]. This finding agrees with a meta-analysis which found that an average of 70 mg/day purified isoflavone aglycone extracts (27–132 mg/day), consumed independently of soy protein, did not significantly lower total or LDL-C in normocholesterolemic menopausal women [18].…”
Section: Interventional Studies Involving Soymentioning
confidence: 99%
“…1, after full text assessment, 69 studies were excluded due to inappropriate study design, inappropriate population/exposure studies, or gender specific estimates missing. The remaining 23 RCTs [15][16][17][18][19][20][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] were included in the review and meta-analysis. In total 1880 postmenopausal women (1130 in intervention arm and 750 in placebo arm) were included in the meta-analysis of 23 RCTs.…”
Section: Characteristics Of Included Rctsmentioning
confidence: 99%
“…The double-blind, placebo-controlled, randomized trial in parallel design with 179 postmenopausal women has been described previously [ 21 ]. The present study refers to a subgroup of women ( n = 60) who received for 12 weeks a commercially available, analytically well-characterized soy IF extract (for details, see [ 21 ], Supplementary Material Table S1 ) in capsule form for 12 weeks. Daily intake was 117.4 mg IF (genistein 49.7%; daidzein 41.4%; glycitein 9.0%).…”
Section: Methodsmentioning
confidence: 99%